A Review on the Reclamation Technologies for Service-Aged Transformer Insulating Oils - Sharin Ab Ghani; Zulkarnain Ahmad Noorden; Nor Asiah Muhamad; Hidayat Zainuddin; Mohd Aizam Talib (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Power transformers are the backbone of electricity transmission and distribution systems throughout the world. The price of power transformers is exorbitant (costing millions of dollars per unit) and therefore, frequent maintenance is necessary to ensure that these systems are highly reliable during their operation. The service life of mineral insulating oils is typically 30 to 40 years for power transformer applications. However, all insulating oils (regardless of their type) are subjected to thermal, electrical and chemical degradation, which will deteriorate the oil-paper insulating system and consequently reduce the capability of the oil as an electrical insulator. For these reasons, service-aged insulating oils are treated by two types of processes (i.e. reclamation and reconditioning) in order to prolong the service life of these oils. Reclamation (regeneration) is used to treat insulating oils with high levels of acidity and sludge. In this paper, a brief review on the reclamation technologies used to treat service-aged insulating oils is presented, covering various aspects such as the standard test methods that need to be complied with, the types of adsorbents used to reduce acidity and sludge of the used insulating oils, as well as the findings of several key studies related to the evaluation of the effectiveness of the reclamation process. This review will indeed benefit researchers and practitioners in this field since it provides an overall picture of the recent progress in reclamation technologies for service-aged transformer insulating oils